2017
DOI: 10.1371/journal.pone.0180724
|View full text |Cite
|
Sign up to set email alerts
|

Role of a novel immune modulating DDR2-expressing population in silica-induced pulmonary fibrosis

Abstract: Micro-injuries associated with chronic inhaled particle exposures are linked with activation of the immune response and are thought to contribute to progression of fibrotic disease. In the pulmonary environment, we have previously demonstrated a heterogeneous population of circulating fibroblast precursors (CFPs), which are defined by expression of the pan-leukocyte marker CD45 and the collagen receptor, discoidin domain receptor-2 (DDR2). This population is derived from the hematopoietic stem cell, expresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Previous studies in our lab have shown that myeloid-derived CD45 + DDR2 + cells home to pathological environments, where they differentiate into fibroblasts and other stromal subsets [ 48 , 50 ]. Recently, myeloid-derived CD45 + DDR2 + cells were also shown to express markers of immune activation, including CD80 and MHC II, in an inflammatory lung model [ 49 ]. These findings led us to examine if a subset of CD45 + DDR2 + cells contributes to inflammation in the adipose tissue of preobese mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies in our lab have shown that myeloid-derived CD45 + DDR2 + cells home to pathological environments, where they differentiate into fibroblasts and other stromal subsets [ 48 , 50 ]. Recently, myeloid-derived CD45 + DDR2 + cells were also shown to express markers of immune activation, including CD80 and MHC II, in an inflammatory lung model [ 49 ]. These findings led us to examine if a subset of CD45 + DDR2 + cells contributes to inflammation in the adipose tissue of preobese mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that a subset of activated CD45 + DDR2 + cell shaves the capacity to skew CD4 + T cells towards a Th17 phenotype [ 49 ]. To determine if adipose tissue from HFD-fed mice triggers CD45 + DDR2 + cells to stimulate T cell cytokine production, sorted CD45 + DDR2 + cells from peripheral blood of control, ND-fed mice were primed in media conditioned by MGAT from HFD- or ND-fed mice and then cultured with CD4 + T cells from control, ND-fed mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This model suffers from a high mortality rate and variability, is prone to survival bias and is claimed to be self-limiting in time 26 . The short timespan over which fibrosis develops and peaks does not allow truly therapeutic testing of interventions with antifibrotic potential, warranting gearing up to alternative, chronic models where fibrosis does not spontaneously resolve, such as irradiation-induced lung fibrosis 27,28 , transgenic mice and silicosis 29 . Silica instillation leads to fibrotic nodules that resemble those seen in patients exposed to environmental triggers such as dust and particulates 6 .…”
Section: Discussionmentioning
confidence: 99%